Substantial clinical benefit and patient acceptable symptom states of the Forgotten Joint Score 12 after primary knee arthroplasty - Heijbel, Siri; W-Dahl, Annette; Nilsson, Kjell G; Hedström, Margareta (Acta Orthopaedica, 2022)
Background and purpose — Knowing how to interpret values obtained with patient reported outcome measures (PROMs) is essential. We estimated the substantial clinical benefit (SCB) and patient acceptable symptom state (PASS) for Forgotten Joint Score 12 (FJS) and explored differences depending on methods used for the estimates. Patients and methods — The study was based on 195 knee arthroplasties (KA) performed at a university hospital. We used 1 item from the Knee injury and Osteoarthritis Outcome Score domain quality of life and satisfaction with surgery, obtained 1-year postoperatively, to assess SCB and PASS thresholds of the FJS with anchor-based methods. We used different combinations of anchor questions for SCB and PASS (satisfied, satisfied with no or mild knee difficulties, and satisfied with no knee difficulties). A novel predictive approach and receiver-operating characteristics curve were applied for the estimates. Results — 70 and 113 KAs were available for the SCB and PASS estimates, respectively. Depending on method, SCB of the FJS (range 0–100) was 28 (95% CI 21–35) and 22 (12–45) respectively. PASS was 31 (2–39) and 20 (10–29) for satisfied patients, 40 (31–47) and 38 (32–43) for satisfied patients with no/mild difficulties, and 76 (39–80) and 64 (55–74) for satisfied patients with no difficulties. The areas under the curve ranged from 0.82 to 0.88. Interpretation — Both the SCB and PASS thresholds varied depending on methodology. This may indicate a problem using meaningful values from other studies defining outcomes after KA. This study supports the premise of the FJS as a PROM with good discriminatory ability in patients undergoing KA.